ACCURACY, FLUENCY AND ARTISTRY – MAIN PRINCIPLES IN DOING TRANSLATION - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, April 2016 Accuracy, fluency and artistry were the three main principles in doing translation that were frequently emphasised by the foremost translator from China, the late Yan Fu, gathered from the book entitled “The Principles of Translation Evolution and Ethics and Other Essays” which touches on the process of doing translation.